Mining the History Sections of Wikipedia Articles on Science and Technology - Kircheis, Wolfgang; Schmidt, Marion; Simons, Arno; Stein, Benno; Potthast, Martin (IEEE/ACM Joint Conference on Digital Libraries (Online), 2023)
Priority conflicts and the attribution of contributions to important scientific breakthroughs to individuals and groups play an important role in science, its governance, and evaluation. Debates and dynamics around these processes are analyzed by science studies. Our objective is to transform Wikipedia into an accessible, traceable primary source for analyzing such debates. In this paper, we introduce Webis-WikiSciTech-23, a new corpus consisting of science and technology Wikipedia articles, focusing on the identification of their history sections. We extract such articles from Wikipedia dumps through iterative filtering of the category network. The identification of passages covering the historical development of innovations is achieved by combining heuristics for section heading analysis and classifiers trained on a ground truth of articles with designated history sections.